THE EFFECTIVENESS OF DEMONSTRATION AND EXPERIMENTATION LEARNING METHODS FOR EMPOWERING PINE FOREST COFFEE FARMERS BENDOSARI VILLAGE PUJON-MALANG INDONESIA - Ani Budi Astuti; N Nurjannah; Luthfatul Amaliana; Wenny Bekti Sunarharum (Erudio Journal of Educational Innovation, 2019)
An effective learning method is very important for the success of a learning goal, especially for the success of learning that involves the village community. The village communities have very diverse abilities and knowledge, in general an activity is carried out in accordance with daily habits, so it is not easily changed. However, the villagers already have a lot of experience, especially related to their daily livelihoods. The characteristics of such objects require an effective learning innovation in order to increase the knowledge they do not yet have. An effective learning method is a form of activity to improve the culture of literacy in the community. The demonstration learning methods and field experiments proposed as learning methods are expected to be in accordance with the characteristics of coffee farmers in Bendosari Village in the context of empowering coffee farmers in Bendosari Village. The purpose of this study is to identify how effective the demonstration learning methods and field experiments for empowering coffee farmers in Bendosari Village, Pujon-Malang Indonesia. The results showed that the demonstration learning method and field experiment very effective in increasing the knowledge and field ability of coffee farmers in Bendosari Village. Increase farmers knowledge and ability by 20%.